Status of State Health Sciences Universities of India: A Webometric Analysis - Rani, Sapna; Lal, Payare; Singh Brar, Kushpreet (Journal of Information and Knowledge, 2018)
Applications of ‘Web technology’ are a subject of concern in this rapidly changing world where creativity and innovation matter. The main objective of this paper is to present the findings of a webometric analysis of websites of state health sciences universities of India. This study was conducted in September 2018 using Alexa Traffic Rank, Google Page Rank and Google search engine. The results of the study indicated that as per the Alexa Traffic Ranking, Dr. N.T.R. University of Health Sciences and Sri Venkateswara Institute of Medical Sciences universities of Andhra Pradesh State were on the top. Ayush and Health Sciences University of Chhattisgarh lead the list of universities in Google Page ranking system. The Nizam’s Institute of Medical Sciences of Telangana State ranked at the top for rich files. The present study provides information to eliminate the barriers to improve websites of state health sciences universities in India to make these websites more effectively fulfil the needs of users.